Systemic exertion intolerance disease diagnostic criteria applied on an adolescent chronic fatigue syndrome cohort: evaluation of subgroup differences and prognostic utility - Tarjei Tørre Asprusten; Dag Sulheim; Even Fagermoen; Anette Winger; Eva Skovlund; Vegard Bruun Wyller (BMJ Publishing Group, 2018)
Objective Existing case definitions for chronic fatigue syndrome (CFS) all have disputed validity. The present study investigates differences between adolescent patients with CFS who satisfy the systemic exertion intolerance disease (SEID) diagnostic criteria (SEID-positive) and those who do not satisfy the criteria (SEID-negative).Methods 120 adolescent patients with CFS with a mean age of 15.4 years (range 12-18 years) included in the NorCAPITAL project (ClinicalTrials ID: NCT01040429) were post-hoc subgrouped according to the SEID criteria based on a comprehensive questionnaire. The two subgroups were compared across baseline characteristics, as well as a wide range of cardiovascular, inflammatory, infectious, neuroendocrine and cognitive variables. Data from 30-week follow-up were used to investigate prognostic differences between SEID-positive and SEID-negative patients.Results A total of 45 patients with CFS were SEID-positive, 69 were SEID-negative and 6 could not be classified. Despite the fact that clinically depressed patients were excluded in the NorCAPITAL project, the SEID-positive group had significantly higher score on symptoms suggesting a mood disorder (Mood and Feelings Questionnaire): 23.2 vs 13.4, difference 9.19 (95% CI 5.78 to 12.6). No other baseline characteristics showed any group differences. When accounting for multiple comparisons, there were no statistically significant differences between the groups regarding cardiovascular, inflammatory, infectious, neuroendocrine and cognitive variables. Steps per day and Chalder Fatigue Questionnaire at week 30 showed no differences between the groups.Conclusion The findings question the discriminant and prognostic validity of the SEID diagnostic criteria in adolescent CFS, and suggest that the criteria tend to select patients with depressive symptoms.